The impact of training intervention on levels of indicator bacteria and prevalence of selected pathogens in raw milk from smallholder women dairy farmers in Central Ethiopia - Beyene, A.M.; Nigatu, S.; Archila-Godinez, J.C.; Amenu, Kebede; Kowalcyk, B.; Degefaw, D.; Mogess, B.; Gelaw, B.; Gizachew, M.; Mengistu, A.; Abdelhamid, A.G.; Barkley, J.; et al. (Elsevier, 2025)
Contamination of milk is a serious public health risk, particularly in developing countries such as Ethiopia. Training is a tool for improving the quality and safety of milk. However, its effect on the microbial quality and safety of milk has not been well documented. This study assessed the impact of training interventions on the microbial quality and safety of milk, with a specific focus on smallholder dairy farms. The study was conducted from January to June 2022 in four locations in Central Ethiopia. Milk samples were collected from 120 dairy farmers one week before and four to six weeks after the training and analyzed for total coliforms, thermotolerant coliforms, Escherichia coli, Shiga toxin-producing E. coli (STEC), Salmonella enterica and Campylobacter jejuni. Total and thermotolerant coliforms were determined by the Most Probable Number (MPN) method; categorized as high (≥1001 MPN/ml), medium (101 to 103 MPN/ml), low (21 to 102 MPN/ml), and very low (≤20 MPN/ml); and analyzed using generalized linear mixed models. Prevalence of E. coli, STEC, S. enterica, and C. jejuni in raw milk samples were 67, 12, 3, and 4% pre-training and 45, 4, 3 and 2% post-training, respectively. The prevalence of E. coli (p = 0.0389) and STEC (p = 0.0005) was significantly lower post-training compared to pre-training. Most samples had total coliform counts exceeding 103 MPN/ml pre-training (71%); this proportion decreased to 62% post-training. The estimated cumulative probability of being in the high category was marginally significantly higher (p = 0.0581) pre-training (76%) compared to post-training (64%). In conclusion, reductions in the detection of some milk quality and safety parameters were observed. However, a considerable proportion of the milk samples were highly contaminated even after the training. Hence, comprehensive, and continued risk mitigation strategies are needed to ensure milk safety for consumers.